Skutki społeczne antropopresji = Social effects of anthropopression - Fiedler, Gabriela Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
According to the World Health Organization (WHO), health is a state of complete phy-sical, psychological, social, and spiritual well-being that depends on a variety of factors. The biggest influence on maintaining the homeostasis of the human body has lifestyle (in 53%) and, next, the living environment (in 21%). Undoubtedly, factors such as air, water, soil, and living organisms in man's surroundings are equally important. The 19th and in particular the 20th century witnessed an intensive growth of industry and transportation, crop intensification, and urbanization.
Keywords: zdrowie; zanieczyszczenie środowiska; smog; globalizacja; metale ciężkie; health; environmental pollution; globalization; heavy metals